2009
DOI: 10.1007/s10549-008-0297-6
|View full text |Cite
|
Sign up to set email alerts
|

Low SAFB levels are associated with worse outcome in breast cancer patients

Abstract: The scaffold attachment factors SAFB1 and SAFB2 have been shown to function as estrogen receptor (ERalpha) co-repressors in breast cancer cells, and to affect many cellular processes such as stress response, RNA processing, and apoptosis. SAFB1 and SAFB2 have also been implicated in breast tumorigenesis: Their shared chromosomal locus at 19p13 is frequently lost in breast cancer, mutations have been identified, and overexpression results in growth inhibition. The purpose of this study was to determine SAFB1/SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 21 publications
3
22
0
Order By: Relevance
“…This study revealed that decreased expression of SAFB was significantly associated with aggressive cellular characteristics of CRC (e.g., poor cellular differentiation, advanced Dukes stage, advanced TNM stage) and with a poorer outcome of patients, suggesting that SAFB might be a tumor suppressor and a prognostic marker of CRC progression. Consistent with our results, the downregulation of SAFB has been reported to be responsible for the metastasis of prostate cancer and poorer outcomes in patients with breast cancer (13,14).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study revealed that decreased expression of SAFB was significantly associated with aggressive cellular characteristics of CRC (e.g., poor cellular differentiation, advanced Dukes stage, advanced TNM stage) and with a poorer outcome of patients, suggesting that SAFB might be a tumor suppressor and a prognostic marker of CRC progression. Consistent with our results, the downregulation of SAFB has been reported to be responsible for the metastasis of prostate cancer and poorer outcomes in patients with breast cancer (13,14).…”
Section: Discussionsupporting
confidence: 92%
“…10), which is involved in inflammation and tumorigenesis and is a source of reactive oxygen species (11,12). Low expression of SAFB is related to the metastasis of prostate cancer and poorer outcomes in patients with breast cancer, which is partly due to the unrestrained activities of the androgen receptor and estrogen receptor a, respectively (13,14). Our preliminary work and a published microarray analysis found that SAFB expression was downregulated in CRC.…”
Section: Introductionmentioning
confidence: 68%
“…The same region was recently linked to hereditary breast cancer in Swedish families; however, this study did not identify germ line mutations in the coding regions of SAFB1 and SAFB2 (20). We have recently reported that SAFB1/SAFB2 protein expression was frequently lost in breast tumors and that this was associated with worse overall survival (21). Mouse embryonic fibroblasts deficient in SAFB1 showed a lack of contact inhibition, increased foci formation, and increased oncogene-induced anchorage-independent growth.…”
mentioning
confidence: 78%
“…SAFB1 mutations were identified in microdissected breast tumours but not in the normal adjacent tissue, and a high loss of heterozygosity (78%) was detected at the SAFB chromosomal locus in invasive breast cancer [111]. Also, low SAFB expression was associated with worse overall survival of breast cancer patients, but did not affect tamoxifen response [112]. Two animal models, MMTV-Wnt-1 oncogenic mice and mice treated with DMBA, were then used to investigate the impact of SAFB1 +/− heterozygosity on the development of mammary tumours [113].…”
Section: Safb Function In Vivo and Possible Roles In Human Diseasementioning
confidence: 98%